Departures from Axisymmetric Balance Dynamics during Secondary Eyewall Formation - Abarca, Sergio F.; Montgomery, Michael T. (Journal of the atmospheric sciences, 2014)
Departures from axisymmetric balance dynamics are quantified during a case of secondary eyewall formation. The case occurred in a three-dimensional mesoscale convection-permitting numerical simulation of a tropical cyclone, integrated from an initial weak mesoscale vortex in an idealized quiescent environment. The simulation exhibits a canonical eyewall replacement cycle. Departures from balance dynamics are quantified by comparing the azimuthally averaged secondary circulation and corresponding tangential wind tendencies of the mesoscale integration with those diagnosed as the axisymmetric balanced response of a vortex subject to diabatic and tangential momentum forcing. Balance dynamics is defined here, following the tropical cyclone literature, as those processes that maintain a vortex in axisymmetric thermal wind balance. The dynamical and thermodynamical fields needed to characterize the background vortex for the Sawyer–Eliassen inversion are obtained by azimuthally averaging the relevant quantities in the mesoscale integration and by computing their corresponding balanced fields. Substantial differences between azimuthal averages and their homologous balance-derived fields are found in the boundary layer. These differences illustrate the inappropriateness of the balance assumption in this region of the vortex (where the secondary eyewall tangential wind maximum emerges). Although the balance model does broadly capture the sense of the forced transverse (overturning) circulation, the balance model is shown to significantly underestimate the inflow in the boundary layer. This difference translates to unexpected qualitative differences in the tangential wind tendency. The main finding is that balance dynamics does not capture the tangential wind spinup during the simulated secondary eyewall formation event.